THE CORRELATION BETWEEN STUDENTS’ READING HABIT AND READING COMPREHENSION IN ENGLISH AS A FOREIGN LANGUAGE - Nining Syafitri (English Education Journal, 2019)
The problem statement of this research was whether there was a correlation between reading habits and students' reading comprehension skills in learning English as a foreign language. The method of the research used a quantitative approach by using a correlational design. Based on R-value (0.588), the correlation between reading habits and students’ reading comprehension skills was moderate, and the linear regression model was Y = -6.758 + 0.605X. Based on the model, it is stated that there was a positive correlation between reading habits and reading comprehension skills in learning English. It was concluded that reading habits and reading comprehension skills had a proportional relationship.